Anti-American movements in Indonesia as presented in Indonesian online media news: violence against American cultural symbols in response to the “War On Terror” - Al Makmun, Muhammad Taufiq; Nuraeni, Ardianna; Afda, Justine Niken (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article aims to explain the impact of George W. Bush’s War on Terror policy toward the direction of anti-American violence movements committed by Muslim groups in Indonesia. The data were collected from factual news presented in three online news sites: www.detik.com, tempointeraktif.com and kompas.com, during 2000-2009, reporting series of violence movement in Indonesia. It is a media studies research employing: (i) socio-cultural approach to see the social condition and cultural values of the muslim-dominated Indonesian society which has long been colored by American cultural influence, (ii) historical approach to trace the radical movement in Indonesia and to understand what War on terror is, and (iii) Kroes’ theory on Americanization and American cultural influence to understand the presence of American cultural symbols in Indonesia. The findings show that American foreign policy of Bush’s War on terror had changed the direction of violence in Indonesia from anti-Christianity movements to anti-American movements. There are three levels of violence conducted by different Muslim groups in Indonesia. Deadly violence attacks in the form of bomb explosions were done by a radical group of Jema’ah Islamiyah connected to Al-Qaeda network. Expelling foreigners were done by organized Muslim militas like Front Pembela Islam (Islam Defenders Front) and Laskar Jihad. Burning American flag and sealing American fast-food franchise in Indonesia, the lowest level of violence, were done by Muslim student organizations conducting demonstration. The movements are identified as responses to War on terror and the targets of the attacks are characterized as American cultural symbols.